Sales Transformation – Quo Vadis, B2B Sales? - Marco Schmäh; Manuel Kern; Oliver Götz (Marketing Review St.Gallen, 2023)
After almost two years of the COVID-19 pandemic, general opinion holds that it has boosted digitalization and turned sales upside down. This article explores whether this is true – and what it means for the future of B2B sales.
Keywords: 650